2004
DOI: 10.1897/02-649
|View full text |Cite
|
Sign up to set email alerts
|

Glycosidation of chlorophenols byLemna minor

Abstract: Metabolic fate of xenobiotics in plant tissues has an important role in the ultimate fate of these compounds in natural and engineered systems. Chlorophenols are an important class of xenobiotics used in a variety of biocides and have been shown to be resistant to microbial degradation. Three chlorophenyl glycosides were extracted from tissues of Lemna minor exposed to 2,4-dichlorophenol (DCP). The products were identified as 2,4-dichlorophenyl-beta-D-glucopyranoside (DCPG), 2,4-dichlorophenyl-beta-D-(6-O-malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 35 publications
1
62
0
Order By: Relevance
“…To our knowledge, however, malonylated triglycosides of volatile compounds have not been described in plants to date. Malonylation of secondary metabolite glycosides might play a role in enhancing metabolite solubility, resistance to glycosidase-driven cleavage, and differential targeting of organic compounds to either the vacuole or the cell wall (Day and Saunders, 2004;Dhaubhadel et al, 2008). Our results, showing that neither dihexose-pentosides of PhP volatiles nor their malonylated forms could be cleaved by endogenous glycosylhydrolases induced upon disruption of both low-and high-PhP volatile fruits, indicate that the addition of the second hexose rather than the malonylation is the primary factor determining the resistance of the low-PhP volatile triglycoside species to endogenous hydrolysis.…”
Section: Emission Of Php Volatiles From Tomato Fruit Upon Tissue Disrmentioning
confidence: 99%
“…To our knowledge, however, malonylated triglycosides of volatile compounds have not been described in plants to date. Malonylation of secondary metabolite glycosides might play a role in enhancing metabolite solubility, resistance to glycosidase-driven cleavage, and differential targeting of organic compounds to either the vacuole or the cell wall (Day and Saunders, 2004;Dhaubhadel et al, 2008). Our results, showing that neither dihexose-pentosides of PhP volatiles nor their malonylated forms could be cleaved by endogenous glycosylhydrolases induced upon disruption of both low-and high-PhP volatile fruits, indicate that the addition of the second hexose rather than the malonylation is the primary factor determining the resistance of the low-PhP volatile triglycoside species to endogenous hydrolysis.…”
Section: Emission Of Php Volatiles From Tomato Fruit Upon Tissue Disrmentioning
confidence: 99%
“…On the other hand, Stroomberg et al [18] determined the structure of a conjugation metabolite of pyrene formed by isopods (Porcellio scaber) and collembolans (Folsomia candida) as pyrene-1-O-(6"-O-malonyl)-glucoside, which is the first reported conjugate formed by animals. On the other hand, malonyl-glycosides are well-known conjugation products formed by plants [19][20][21][22][23][24]. Glucose conjugates formed by various plants are often further conjugated by malonic acid or pentosyl units of hemicellulose, such as apiose or xylose, and form glucose-malonate or glucose-pentosyls [19][20][21][22][23][24].…”
Section: The Role Of Glucose-sulfate Conjugation Formed By Freshwatermentioning
confidence: 99%
“…On the other hand, malonyl-glycosides are well-known conjugation products formed by plants [19][20][21][22][23][24]. Glucose conjugates formed by various plants are often further conjugated by malonic acid or pentosyl units of hemicellulose, such as apiose or xylose, and form glucose-malonate or glucose-pentosyls [19][20][21][22][23][24]. Day and Saunders [23] demonstrated roles of these additional conjugation processes as signals of sequestration of phase-2 metabolites in the plant cell (phase-3 processes for plants).…”
Section: The Role Of Glucose-sulfate Conjugation Formed By Freshwatermentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of duckweed for uptaking organic compounds (including phenolic substances) is a well-known phenomenon, which determines the use of these plants as effective phytoremediation agents (Mkandawire and Dudel, 2007). Studies on chlorophenols showed that these compounds are effectively incorporated into the vacuoles and cell walls of Lemna minor (Day and Saunders, 2004). However, an experimental test performed by Yamaga et al (2010) showed that continuous removal of phenol from the water is not only related to plant uptake, but can be attributed to the beneficial symbiotic interaction between duckweed rhisosphere and bacteria.…”
Section: Discussionmentioning
confidence: 99%